SOCIO-ECONOMIC CONDITIONS OF BU TRABA A SETTLEMENT ON THE COASTAL STRIP OF CYRENAICA - Meliczel, Hans (Dirasat in Economics and Business, 1967)
SOCIO-ECONOMIC CONDITIONS OF BU TRABA A SETTLEMENT ON THE COASTAL STRIP OF CYRENAICA